Factors Related to Prevention Behavior of COVID-19 Transmission among Pregnant Women - Mila Oktaviani; Rini Kundaryanti; Shinta Novelia (Nursing and Health Sciences Journal (NHSJ), 2022)
Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) is a new virus that can cause lung disease and death. The disease is more common in the elderly and in individuals with cardiologic, respiratory, renal, and metabolic comorbidities. This study aimed to determine the factors related to the prevention behavior of Covid-19 transmission among pregnant women at PMB Midwife R. Agustina and PMB Midwife Wiwi Widaningsih. The research design used was Cross Sectional. The population used was all pregnant women in trimesters 1-3 which consisted of 100 people in July-August 2021.The variables of this study were knowledge, attitudes, sources of information, the role of health workers and the behavior of preventing the transmission of COVID-19 in pregnant women. The research instrument used in the study was a questionnaire. The data analysis used is univariate analysis and bivariate analysis. The results showed that out of 100 respondents, 55 (55.0%) respondents had good knowledge, 57 (57.0%), 65 (65.0%) respondents used electronic sources of information, and 55 (55.0%) respondents had good preventive behavior. and 45 (45.0%) respondents had poor preventive behavior. There was a relationship between knowledge (p-value 0.000 OR 3.682), attitudes (p-value 0.000 OR 5.308), and sources of information (p-value 0.002 OR 4.460) with the behavior of preventing the transmission of COVID-19 in pregnant women. This results can be used as a reference to improve mindset and knowledge and make additional knowledge during a pandemic. Health care provider need to educate pregnant women regarding prevention behavior of covid-19 behavior.